2020
DOI: 10.1055/s-0040-1718760
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Histones Inhibit Fibrinolysis through Noncovalent and Covalent Interactions with Fibrin

Abstract: Histones released into circulation as neutrophil extracellular traps are causally implicated in the pathogenesis of arterial, venous, and microvascular thrombosis by promoting coagulation and enhancing clot stability. Histones induce structural changes in fibrin rendering it stronger and resistant to fibrinolysis. The current study extends these observations by defining the antifibrinolytic mechanisms of histones in purified, plasma, and whole blood systems. Although histones stimulated plasminogen activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 51 publications
1
36
0
4
Order By: Relevance
“…In general, denser clots with smaller pores and more closely packed fibers are more resistant against fibrinolysis; however, several fibrin structure modifiers exert direct effects on the efficiency of the plasminogen/plasmin system, which could add up or perhaps override the anticipated effects based on the structural changes. Histones favor lateral aggregation of protofibrils and are covalently cross‐linked to fibrin by FXIIIa resulting in a more plasmin‐resistant clot structure; moreover, they compete for plasmin as alternative substrates 36 . DNA interacts directly with plasmin and fibrin forming an unproductive ternary plasmin‐DNA‐fibrin complex, whereas polyphosphates may shield positively charged plasminogen binding sites in fibrin leading to hampered plasminogen activation 8,20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, denser clots with smaller pores and more closely packed fibers are more resistant against fibrinolysis; however, several fibrin structure modifiers exert direct effects on the efficiency of the plasminogen/plasmin system, which could add up or perhaps override the anticipated effects based on the structural changes. Histones favor lateral aggregation of protofibrils and are covalently cross‐linked to fibrin by FXIIIa resulting in a more plasmin‐resistant clot structure; moreover, they compete for plasmin as alternative substrates 36 . DNA interacts directly with plasmin and fibrin forming an unproductive ternary plasmin‐DNA‐fibrin complex, whereas polyphosphates may shield positively charged plasminogen binding sites in fibrin leading to hampered plasminogen activation 8,20 …”
Section: Discussionmentioning
confidence: 99%
“…Histones favor lateral aggregation of protofibrils and are covalently cross-linked to fibrin by FXIIIa resulting in a more plasmin-resistant clot structure; moreover, they compete for plasmin as alternative substrates. 36 DNA interacts directly with plasmin and fibrin forming an unproductive ternary plasmin-DNA-fibrin complex, whereas polyphosphates may shield positively charged plasminogen binding sites in fibrin leading to hampered plasminogen activation. 8,20 Despite the size-, charge-, and chemical nature-dependent structural and biomechanical effects discussed above, most polyanions showed a rather uniform, but charge-dependent, prolongation of fibrinolysis with plasmin incorporated in fibrin-histone clots.…”
mentioning
confidence: 99%
“…It appears that the controversial effects of histones on the fibrinolytic system are relevant for sepsis-induced DIC. Early studies have consistently revealed that histones could accelerate fibrin polymerization and enhance clot structure rendering it stronger and resistant to fibrinolysis, which could be neutralized by histone-binding low-molecular-weight heparin, or FXIIIa inhibitors (70)(71)(72). On one hand, noncovalent histone-fibrin interactions induce lateral aggregation of fibrin protofibrils and increase fibrin-fiber thickness, giving the fibrin network increased mechanical stability.…”
Section: Impaired Fibrinolysismentioning
confidence: 99%
“…On one hand, noncovalent histone–fibrin interactions induce lateral aggregation of fibrin protofibrils and increase fibrin-fiber thickness, giving the fibrin network increased mechanical stability. On the other hand, histones also inhibit plasmin as competitive substrates to delay fibrinolysis, and protect fibrin from plasmin digestion through their covalent interactions with fibrin, catalyzed by activated coagulation factor FXIII (FXIIIa) ( 70 ). On the contrary, Fabrizio et al argued that histones strongly accelerated single-chain urokinase-type plasminogen activator (scu-PA)-driven clot lysis through the enhancement of scu-PA to urokinase-type plasminogen activator conversion, mediated by factor seven activating protease ( 73 ).…”
Section: Immunopathological Role Of Circulating Histones In Sepsismentioning
confidence: 99%
“…It must be emphasized, that our primary goal was to find assay conditions where fibrinolysis kinetics are optimally influenced by the addition of cfDNA and histones. The mechanisms behind the observed effect of cfDNA and histones resulting in prolongation of clot lysis are complex (14,37). Among others, the addition of cfDNA promotes the formation of densely packed networks of thick fibers less susceptible to plasmin digestion, while the addition of histones competitively inhibits plasmin and delays fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%